Upaya Pengembangan Guru Taman Pendidikan Al-Qur’an - Wahyu Anis Amanullah; Sutarman Sutarman (Universitas Muhammadiyah Ponorogo, 2021)
This study examines the efforts to develop the Anwar Rasyid Al-Qur’an Education Park teacher, Gondokusuman District, Yogyakarta City in 2020. This study aims to analyze and describe the efforts to develop Anwar Rasyid Quran Education Park (TPA) teachers. The results showed that teacher development efforts at Anwar Rasyid TPA had been carried out with education and training including tahsin, public speaking, discussions between teachers, tahfidz boarding schools, syahadah exams and delegation of tasks. The supporting factors in the effort to develop Anwar Rasyid TPA teachers are teacher activity, clear division of work and authority, discipline from teachers and support from both the mosque takmir and santri guardians. The inhibiting factor is financial, especially funding problems and the absence of indigenous teachers who teach and manage Anwar Rasyid's TPA. The benefits of teacher development on the quality of education make teachers and students more disciplined, teachers can develop their potential through the KBM process, students have good quality reading of the Koran, students have memorized the Koran and also have akhlaqul kharimah. In addition, it also has an impact on the sense of ownership and responsibility for the mandate given.